Pelatihan dan Pendampingan Tentang Keamanan Produk Pangan Industri Rumah Tangga Usaha Mikro di Desa Kalawat Kecamatan Kalawat.: Training and Mentoring regarding Food Product Safety for Home Industry and Micro Small in Kalawat Village, Kalawat District - Rotinsulu, Tri Oldy; Kindangen, Paulus; Kumenaung, Anderson (Sam Ratulangi University, 2025)
This service activity aims to provide training and assistance to Micro and Small Enterprises on the Safety of Household Industrial Food Products in Kalawat Village, Kalawat District. The purpose of this service is to provide an introduction to the importance of having knowledge and information about food safety for household industry players who are just starting a business or who are already running their businesses. The community service methods used are counseling, training and mentoring. The results obtained from this activity are that the Kalawat MSME industry business actors gain understanding, skills in processing food properly and safely. The increase in knowledge from the evaluation of knowledge and information about food safety for micro and small business actors in the household industry increased by 90%. Around 90 percent of the trainees have understood the purpose and purpose of this service activity. The results of the posttest for the training 89 percent of the trainees have understood food safety, the mechanism for managing food household industry permits. ABSTRAK Kegiatan pengabdian ini bertujuan memberikan pelatihan dan pendampingan kepada Usaha Mikro Kecil tentang Keamanan Produk Pangan Industri Rumah Tangga di Desa Kalawat Kecamatan Kalawat. Tujuan pengabdian ini memberikan pengenalan tentang pentingnya memiliki pengetahuan dan informasi tentang keamanan pangan bagi pelaku industri rumah tangga yang baru memulai usaha ataupun yang sudah menjalankan usahanya. Metode pengabdian kepada masyarakat yang digunakan adalah penyuluhan, pelatihan dan pendampingan. Hasil yang diperoleh dari kegiatan ini para pelaku usaha industri UMKM Kalawat mendapatkan pemahaman, ketrampilan dalam mengolah pangan dengan baik dan aman. Peningkatan pengetahuan hasil evaluasi terhadap pengetahuan dan informasi tentang keamanan pangan bagi pelaku usaha mikro dan kecil di Industri rumah tangga meningkat 90%. Sekitar 90 persen peserta pelatihan telah memahami maksud dan tujuan kegiatan pengabdian ini. Hasil postest untuk pelatihan 89 persen para peserta pelatihan telah memahami mengenai keamanan pangan, mekanisme pengurusn ijin industri rumah tangga pangan.